Employee Performance and Influenced By Competency, Leadership, and Commitment - Nazifah Husainah (Dinasti International Journal of Education Management And Social Science, 2023)
The objective of this study is to examine the impact of competence, leadership, and organizational commitment on performance. A total of 471 employees were selected as the sample for this research. The research design utilized was descriptive and focused on establishing causal relationships. Data analysis was carried out using SPSS version 5. The research instruments included data engineering analysis and hypothesis testing. The findings of the study indicate that the combined variables of competence, leadership, and commitment account for 81.6% of the variance in employee performance. Furthermore, it was observed that there is a significant and tangible influence of competence, leadership, and commitment on employee performance when these factors are considered simultaneously.